Major Risk Factors Faced by Women During Pregnancy in Kathmandu Metropolitan City - Pokharel, Sharmila (Tribhuvan University Journal, 2020)
Giving birth to another person’s life is not a minor matter. Pregnancy canals be a risky condition that can lead to death, while some die; some survive a short-lived battle of death happens. This study aimed to identify risk factors for female pregnancy and find out the major pregnancy problems faced by pregnant women. Forty six women who teach in the Faculty of Education in Kathmandu, Nepal were taken as a sample size. A descriptive quantitative method was used where a structured questionnaire was filled with their consent. IBM SPSS 20version was used for statistical analysis which calculated the risk estimates odd ratio and confidence interval at 95%; the only normal frequency was tabulated and analyzed. This study finds that many risk factors in the pregnancy period like; health problems, lack of adequate knowledge, lifestyle exposure, and age factors. Hence women should be accompanied by their partner and family and society and support them during pregnancy time.